Pengaruh Hubungan Antar Manusia Dan Kondisi Lingkungan Terhadap Etos Kerja Karyawan Di Nuju Coffee Bandar Lampung - Maulida, Mutiara Putri; Alam, Iskandar Ali (Politeknik Negeri Ambon, 2025)
This research aims to explore the extent to which interpersonal relationships and environmental conditions affect the work ethic of employees working at Nuju Coffee in Bandar Lampung. To achieve this aim, the study adopted a quantitative methodology characterized by a correlational research design suited for examining the relationships between variables. The total population for this study consisted of 210 employees, from which a sample of 68 respondents was selected using the Slovin formula to ensure an appropriate representation. Data collection methods included direct observation and administering structured questionnaires designed with a Likert scale to measure responses. The findings indicated that both interpersonal relationships and environmental factors positively and statistically significantly influence employees' work ethic, underscoring their importance in fostering productive workplace behaviors. Of the 68 respondents, 49 categorized interpersonal relationships as very good, 45 respondents categorized environmental conditions as very good, and 52 respondents categorized work ethic as strongly agree. This study concludes that management needs to improve communication between employees and improve work environmental conditions to enhance employee work ethic.